Rancang bangun Sistem Informasi Pelayanan Masyarakat Berbasis Web Pada Desa Sambeng Kulon Kabupaten Banyumas - Supriatiningsih Supriatiningsih; Mahmud Safudin; Eko Yulianto (Universitas Bina Sarana Informatika, 2019)
Abstract: In the current era of globalization, information technology advancing rapidly. Developments in information technology have led to a new revolution in the form of a conventional shift working system into the digital era. This change has also changed the perspective of each person in doing various activities one of which is on the activities of government agencies. The number of managed data and the need for rapid delivery of information in the public service activities at the Village Office Sambeng Kulon, Banyumas District. Public services such as the pcopulation census should be carried out continuously, continuous, timely and accurate. Because every day people must have come to the village office for various purposes such as making a written request KTP, KK, cover letters moving, death certificates, birth certificates and a letter was not able to take a long time and every resident who apply for the required letter is not uncommon back to the house to complete the necessary requirements for at least information about the documents needed to make the required letter. It is of course not efficient. To solve the above problem, a computerized system should be applied over existing systems to ensure the accuracy of the data. With so all processes can be fully realized public services effectively and efficiently because it does not have to require a longer time. The system development method used in designing this information system is the systemwaterfall method. Keywords: Information Systems, Website Services System, Waterfall